Pembentukan Intisari Topik secara Otomatis dalam Suatu Paragraf dengan Model Vector Space Model - Muhammad Erwin Ashari Haryono (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
This paper is the implementation of both topic model text summarization and Information retrieval model.This paper conducted on identyfing topical coherency inside one paragraphs of an expository text. Expositorytext is a kind of text which is intended for publicity such as journal, news etc. Many expository text consist oflong sequences of paragraphs with very little structural demarcation, while others consist of sequences ofparagraphs which still discuss the same topic. This paper uses vector space model to identify topical coherencybetween paragraphs. Vector space model measures lexical similarity between adjacent paragraphs, withassumption that the more similar two adjacent paragraphs are, the more likely it is that the current topiccontinues. We use expository text from one week daily local newspaper “Kedaulatan Rakyat” from cultural andeducational topic. We choose 20 sample for testing our method, the result is not very good for the precisionamong main idea and its paragraphs (approximately 60 percentage success and 40 failured).Keyword: expository text, topical coherency, vector space model model